Effect of neoadjuvant therapy on textbook outcomes in minimally invasive rectal cancer surgery - Guiqi Zhang; Shiquan Pan; Jiashun Wei; Jie Rong; Yuan Liu; Dongbo Wu (World Journal of Surgical Oncology)
Abstract Aim Textbook outcome (TO), a combined quality indicator, encompasses key postoperative indicators such as the absence of complications, R0 resection, and no prolonged length of day. It has been suggested to be of additional value over single outcome parameters in short-term outcomes of surgical treatment. The main objective of this research was to assess the relationship between TO and neoadjuvant therapy (NT), thereby providing insights into NT’s role in surgical quality. Method Patients who underwent minimally invasive rectal surgery were enrolled between January 2019 and June 2024. TO was defined as achieving R0 resection, at least 12 lymph nodes harvested, no adverse outcomes (Clavien–Dindo score ≥ 3, readmission, or mortality within 30 days), and length of stay within the ≤ 75th percentile for the treatment year. The relationship between TO and NT was analyzed using regression analyses. Subgroup analysis and hierarchical regression were conducted to investigate potential influencing factors and interactions. Results 405 patients were enrolled, with 204 achieving TO. NT was associated with a reduction in TO (OR: 0.37, 95% CI: 0.21 ~ 0.65, p < 0.001), while robotic surgery (OR: 2.88, 95% CI: 1.62 ~ 5.11), total laparoscopic surgery (OR: 2.79, 95% CI: 1.71 ~ 4.56), enhanced recovery after surgery (OR: 1.62, 95% CI: 1.02 ~ 2.59), and stoma (OR: 1.87, 95% CI: 1.18 ~ 2.96) were associated with an increased rate of TO. The impact of NT on TO varied depending on surgery duration; prolonged surgical time exacerbated the negative effect of NT on TO. This observation was consistent with a significant interaction effect. Conclusion NT is associated with a lower TO rate, especially in patients with prolonged surgical time. Robotic surgery, total laparoscopic surgery, enhanced recovery after surgery, and stoma can improve achieve TO.